2012
DOI: 10.1017/s1751731111002527
|View full text |Cite
|
Sign up to set email alerts
|

The influence of casein and urea as nitrogen sources on in vitro equine caecal fermentation

Abstract: To access the fermentative response of equine caecal microbial population to nitrogen availability, an in vitro study was conducted using caecal contents provided with adequate energy sources and nitrogen as limiting nutrient. Two nitrogen (N) sources were provided, protein (casein) and non-protein (urea). Caecal fluid, taken from three cannulated horses receiving a hay-concentrate diet, was mixed with a N-free buffer-mineral solution. The influence of four N levels (3.7, 6.3, 12.5 or 25 mg of N in casein or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…The fact that horses used in this study were fasted may also have contributed to the results. However, recent studies from our team using PB as microbial markers in cecal contents of cannulated, fed horses indicated similar PB and adenine:guanine ratio as those observed in this study (Santos et al, 2012). Total FA concentration of bacterial biomass did not differ between PAB and SAB, which is a different pattern that that observed in the rumen where FA concentration of SAB is consistently greater than PAB (Merry and McAllan, 1983;Bessa et al, 2009).…”
Section: Resultssupporting
confidence: 62%
“…The fact that horses used in this study were fasted may also have contributed to the results. However, recent studies from our team using PB as microbial markers in cecal contents of cannulated, fed horses indicated similar PB and adenine:guanine ratio as those observed in this study (Santos et al, 2012). Total FA concentration of bacterial biomass did not differ between PAB and SAB, which is a different pattern that that observed in the rumen where FA concentration of SAB is consistently greater than PAB (Merry and McAllan, 1983;Bessa et al, 2009).…”
Section: Resultssupporting
confidence: 62%
“…The concentration of NH 3 -N in in vitro fermentation assays is inversely proportional to the concentration of microbial protein (Cone et al, 1997). In the present study, the NH 3 -N values observed after 72 h were greater than those observed by Santos et al (2012), possibly due to the greater true protein fermentation present in the substrate.…”
Section: Discussioncontrasting
confidence: 61%
“…The microbial population present in the cecum uses non-protein N to generate volatile fatty acids (VFA) in detriment of population growth as a metabolic strategy (Santos et al, 2012). However, the quantification and identification of groups that would benefit from this nitrogen source were not carried out (Santos et al, 2012). The concentration of NH 3 -N in in vitro fermentation assays is inversely proportional to the concentration of microbial protein (Cone et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high sugar content, colloidal suspension, vitamins, and nitrogen compounds, molasses is often used in the production of microorganisms 26 . Urea was selected as a nitrogen source since it has been utilized in the cultivation of microorganisms by several authors 35 , 36 . In our media evaluation experiments, molasses and urea were found to be suitable sources of carbon and nitrogen, respectively.…”
Section: Discussionmentioning
confidence: 99%